Religion, Justice and Women: the Views of Dominican Christian Mystics Meister Eckhart and Franciscan Bonaventura - Is Bryan Bowo Pangestu; Falenrius Nderi; Agustinus Dwi Handono; JB. Heru Prakosa (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Mysticism was an interesting and fascinating phenomenon in medieval times. In that century, the scientific interest and views on mysticism that experienced high intensity, especially in its literature, also became a challenge from both religious and epistemological sides. This is not surprising, since visionary stories reflecting transcendental experiences associated with forms of religious spirituality could not be understood by (modern) rationality. Even today, rationalism and empiricism are popular for determining justice that materializes from development and knowledge in a measurable way. This also creates a dilemma, where the orientation of rationalism and empiricism emphasizes results rather than the relationship between humans and the Divine. The views of Christian mystics MeisterEckhart and Bonaventure provide an overview of the relationship between mysticism and social life. This article discusses the views of Dominican mystic MeisterEckhart and Franciscan mystic Bonaventure on religion, justice and women. These two Christian mystics emphasize the dimensions of human unity with God, the position of human beings, and human relations. At a time when the development of rationalism and empiricism is massive, mystical experience becomes one of the alternative views to revisit the relationship between humans that comes from unity with the Divine in the perspective of Religion, Justice and Women. This scientific work is studied using the literature method.